The Implementation of Google Platform-Assisted E-Learning to Improve Students’ Mathematical Understanding on Junior High School - Candra, Riki; Hendriana, Heris; Supriatna, Tatang (IKIP Siliwangi, 2026)
The rapid development of digital technology has transformed the educational landscape, encouraging the integration of online learning platforms in classroom instruction. In mathematics education, e-learning tools offer opportunities to enhance students’ conceptual understanding through interactive and accessible digital media. This study aims to determine the improvement in students’ understanding of mathematical concepts through the implementation of Google Platform-assisted e-learning using Google Meet and Google Forms at SMP Negeri 2 Seruway. The research employed a quantitative approach with a pre-experimental method and a One Group Pretest–Posttest design. The population comprised all eighth-grade students (58 students), with class VIII-A consisting of 16 students selected as the sample. Learning activities were conducted using Google Meet for synchronous sessions and Google Forms for formative assessments on probability material. Data were collected through pretest and posttest instruments, and the results were analyzed using descriptive statistics and correlation tests. Findings revealed an increase in the average score from 53.94 before the treatment to 74.25 after. The hypothesis test used the t-test formula, obtaining a t-count value of 8.26, which was greater than the t-table value of 2.13 at a significance level of α = 0.05. These results indicate a significant improvement in students’ mathematical understanding after implementing e-learning through Google Meet and Google Forms. In conclusion, the use of Google-based e-learning effectively supports students’ conceptual understanding and promotes a more engaging mathematics learning experience.